(untitled) (Scientific journal of the Fergana State University, 2023)
This article states that human dignity and rights embody the concepts of universality, national state, and law, and that the purpose of learning philosophy is to understand the world, to achieve ideological and spiritual perfection, and to study the laws of rational living.